The significance of amelogenin loci from toothpicks as forensic evidence for sex determination - Arofi Kurniawan, DDS, PhD; Beta N. Rizky, DDS, MSc; An'nisaa Chusida, DDS, MDSc, PhD; Beshlina F.W.R. Prakoeswa, DDS, MSc; Salma A. Athalia, BDS; Stefani T.J. Malau, BDS; Aspalilah Alias, DDS, PhD (Journal of Taibah University Medical Sciences, 2023)
الملخص: أهداف البحث: أصبح تحليل الحمض النووي الريبي منقوص الأكسجين هو المعيار الذهبي في التعرف على الأفراد من خلال فحص الطب الشرعي. هناك العديد من المصادر الأولية والثانوية لعينات الحمض النووي في مجال الطب الشرعي. تشمل المصادر الثانوية العناصر التي يستخدمها الشخص مثل الملابس وفرشاة الأسنان وأعواد الأسنان. في الدول الآسيوية مثل كوريا واليابان وإندونيسيا، ينتشر استخدام أعواد الأسنان. يمكن استخدام طرف عود الأسنان المستخدم في تنظيف جزيئات الطعام في المناطق بين الأسنان لالتقاط عينات من الحمض النووي من اللعاب. استخدام عينات اللعاب لتحليل الحمض النووي في تحديد الجنس يعتمد على التكرار الترادفي القصير مع موضع الأميلوجينين. الغرض من هذه الدراسة هو فحص تركيز ونقاء الحمض النووي على أعواد الأسنان كدليل في التحقيقات الجنائية، بالإضافة إلى إمكانية استخدامه لتحديد الجنس. طرق البحث: تم توجيه ثمانية أشخاص لتنظيف الجانب البيني لأسنانهم الخلفية باستخدام عود أسنان. علاوة على ذلك، تم الاحتفاظ بكل عينة من أعواد الأسنان لمدة صفر يوما (كعنصر تحكم)، و 14 يوما، و 20 يوما. تم تحديد النقاء وتركيز الحمض النووي لكل عينة من خلال فحص الحمض النووي. بعد تحديد تركيز ونقاء الحمض النووي من كل عينة، تم إجراء الرحلان الكهربائي في مواضع الأميلوجينين لتحديد الجنس. النتائج: أظهرت هذه الدراسة أن متوسط تركيز الحمض النووي في أعواد الأسنان تراوح بين 425.25 - 796.25 ميكروغرام / مل. متوسط نقاء الحمض النووي في هذه الدراسة يتراوح بين 1.09 - 1.13 ميكروغرام / مل. ينتج جين الأميلوجينين 112 زوج قاعدي و 116 زوج قاعدي من المضخم النووي من الكروموسومات إكس و واي. الاستنتاجات: يمكن تحديد الجنس باستخدام الحمض النووي باستخدام موضع الأميلوجينين، وهو بروتين موجود في الكروموسومات الجنسية (إكس و واي). لا يزال من الممكن استخدام قيمة تركيز الحمض النووي لعود الأسنان في هذه الدراسة لدعم الطب الشرعي بعد 20 يوما في درجة حرارة الغرفة. Abstract: Objective: DNA analysis has become the gold standard of all identification methods in forensic science. There are several primary and secondary sources of DNA samples in the field of forensics. Primary sources can be obtained directly from individuals, whereas secondary sources of DNA samples include items used by someone such as clothes, toothbrushes, and toothpicks. In Asian countries such as Korea, Japan, and Indonesia, toothpicks are often used, as the tip of toothpicks used to clear food particles in the interdental regions can be utilized to capture DNA samples from saliva. The use of saliva samples for DNA analysis in sex identification is based on short tandem repeats with the amelogenin (AMG) locus. The purpose of this study was to examine the concentration and purity of DNA on toothpicks as evidence in criminal case investigations, as well as its potential as sex determination material. Methods: Eight subjects were instructed to clean the interproximal side of their posterior teeth using a toothpick. Each toothpick sample was kept for 0 days (as a control), 14 days, and 20 days. The purity and DNA concentration of each sample were determined through DNA examination. After determining the concentration and purity of DNA from each sample, electrophoresis of the AMG loci was performed for sex determination. Results: This study showed that the average concentration of DNA on toothpicks ranged from 425.25 to 796.25 μg/ml, and the average purity of DNA ranged from 1.09 to 1.13 μg/ml. The AMG gene produces 112 and 116 base pair amplicons from the X and Y chromosomes. Conclusion: Sex determination using DNA can be done using AMG loci, a protein found on the sex chromosomes (X and Y). The value of DNA concentration on toothpicks could be used to support forensic identification after 20 days at room temperature.